P Perancangan Sistem Absensi Digital dan Monitoring Kehadiran dan Lembur di PT. TRIKARSA BAHTERA ABADI - Darmawan, Dimas Bagus; Septiadi, Robby; Saputra, Rendy Wijaya; Haryono, Wasis (Journal TIFDA (Technology Information and Data Analytic), 2025)
Manual attendance systems that are still used in many construction companies often face obstacles such as data manipulation, late recapitulation, and the absence of real-time worker location validation. This study aims to design and implement a web-based digital attendance system with GPS validation and photo documentation to improve the efficiency and accuracy of recording project worker attendance and overtime. The system was developed using the Waterfall approach which includes needs analysis, system design, code implementation, testing, and maintenance. The implementation results show that the system can record attendance and overtime accurately, and facilitate monitoring by project admins through an interactive dashboard. The system also provides separate user roles such as admin, finance, SEM, owner, and workers, each of which has access to relevant features. With this system, the process of monitoring and decision-making related to attendance management becomes faster, more transparent, and more integrated.